The Role of Affect as a Mediator between Coping Resources and Heart Rate Variability among Older Adults. Issue 2 (15th March 2022) - Pinto, Galit; Greenblatt-Kimron, Lee; Marai, Ibrahim; Lorber, Avraham; Lowenstein, Ariela; Cohen, Miri
ABSTRACT: Background: Heart rate variability (HRV) has been suggested as an indicator of capacity to adapt effectively to physiological or environmental challenges and of physical and psychological health in old age. Aims: The study assessed levels of high-frequency HRV (HF-HRV) among older adults in relation to positive and negative affect and the mediating role of positive and negative affect in the association between coping resources (perceived social support and sense of mastery) and HF-HRV.Method: Participants were 187 men and women in three assisted-living residences who were independent in activities of daily living (93.4% participation rate). The participants completed sense of mastery, multidimensional scale of perceived social support, and positive and negative affect questionnaires. HF-HRV was derived from electrocardiography data measured by a Holter monitoring device for 15 minutes.Results: The empirical model showed good fit indices indicating that higher HF-HRV was associated with lower negative affect, and negative affect mediated the association between perceived social support and HF-HRV. In addition, perceived social support and sense of mastery were associated with higher positive affect and lower negative affect.Conclusions: Although this was a cross-sectional study, it suggests that HF-HRV may be a link between affect and health in old age. It also suggests the importance of identification and intervention with older adults and their support systems to reduce negative affect.